A Brief Review of Current Literature on Spontaneous Coronary Artery Dissection in Young, Healthy Women: A Case Series of Three Patients - Nihar Jena; Sreekant Avula; Deepak Chandramohan; Shreya Tiwary; Prashanth Reddy Yella; Bhavin Patel; Kirit Patel (Annals of Internal Medicine: Clinical Cases)
This case series presents 3 middle-aged female patients who were diagnosed with spontaneous coronary artery dissection by invasive and noninvasive measures. Spontaneous coronary artery dissection (SCAD) is usually a disruption of the intima, leading to the creation of a false lumen and flow disruption, hematoma, thrombus formation, and ultimately, myocardial ischemia. The mechanism involves spontaneous hematoma formation or intimal tear due to many factors. Due to the lack of guidelines, varied treatment strategies were adopted with favorable outcomes. The authors describe a concise review of SCAD, reviewing the current literature and expert consensus.